Solid-state and solution studies of bis-carboxylate binding by bis-amidinium calix[4]arenes - Camiolo, S.; Gale, P.; Ogden, Mark; Skelton, B.; White, A. (Royal Society of Chemistry, 2001)
Bis-amidinium calix[4]arene receptors were shown to coordinate bis-carboxylate anions in DMSO solution; the crystal structure of the malonate salt of one of the receptors revealed a number of different amidinium carboxylate interactions, demonstrating the propensity of these species to form complex hydrogen bonding networks.